A Defense Mechanism Based on Improved Allocation Strategy of VMs Co-Resident Attack in Power Cloud Platform - Li, Yuancheng; Zhang, Pan; Li, Daoxing; Zeng, Jing (Recent Advances in Computer Science and Communications, 2021)
Background: Cloud platform is widely applied in the field of electric power. Virtual machine co-resident attack is one of the fundamental security threats to the existing power cloud platform. Objective: This paper addresses a mechanism so as to defend virtual machine co-resident attack on power cloud platform. Methods: Our defense mechanism wields the DBSCAN algorithm to classify the results through the random forest and adopted improved virtual machine deployment strategy which combines the advantages of random round robin strategy and maximum/minimum resource strategy so as to deploy virtual machines. Results: We made a simulation experiment on power cloud platform of State Grid and verified the effectiveness of proposed defense deployment strategy. Conclusion: After the virtual machine deployment strategy is enhanced, the coverage of the virtual machine is remarkably reduced, which proves that our defense mechanism achieves some effect of defending the virtual machine from virtual machine co-resident attack.
Keywords: allocation strategy